Investigating the application of CFA in the liveability assessment of public low-income housing in Nigeria - Sule, Abass Iyanda; Mohit, Mohammad Abdul (Kulliyyah of Architecture, International Islamic University Malaysia, 2015)
Studies on the liveability of Nations/Cities or neighbourhoods have been on the increase due to their perceived aftermath significant contributions to the quality of life. In this study, the liveability dimensions and attributes were developed based on the previous studies and experts opinions to assess the level of living conditions in the public low-income housing estates in Minna, Niger State, Nigeria. The focus of this paper is to explore the liveability dimensions and attributes reliability and to validates its usefulness in determining the liveability of the selected housing estates. It is presumed that not all identified liveability dimensions and attributes variables in the extant literature will be effective in measuring liveability in a cultural context like Nigeria. The data used for this study came from survey questionnaire administered to the residents of the selected three housing estates. Prior to the confirmator factor analysis (CFA), the Cronbach’s Alpha result obtained supported four-factor constructs. The variance explained as obtained from exploratory factor analysis (EFA) was good (67%). The CFA conducted led to the construction of an 18 items measurement. This paper contributed to the empirical study of liveability of housing/residential estates in terms of establishing the reliability and validity of the measurement constructs. Hence, it suggests that CFA analysis even with four-factor constructs can be used in future researches.